Hypnic headache: A review of clinical features, therapeutic options and outcomes. (September 2014) - Liang, Jen-Feng; Wang, Shuu-Jiun
Background: Hypnic headache (HH), first reported in 1988, is a rare sleep-related headache disorder. In 2013 a new diagnostic criteria was proposed for HH in the International Classification of Headache Disorders, the third version beta (ICHD-3β). Purpose: This review aimed to update the clinical characteristics, therapeutic options and clinical outcomes in patients with HH and also validate the new diagnostic criteria. Methods: Based on a literature search in the major medical databases, we analyzed all case reports or case series on HH that have been published since the first description by Raskin. Except for symptomatic patients, all reported patients were included regardless of which diagnostic criteria were adopted. Four studies that reported the field-testing results of the ICHD-2 criteria were selected to validate the new ICHD-3β criteria. Results: In total, 250 adult and five childhood patients are described in this review. The majority of patients were elderly and their ages of onset were typically more than 50 years old (92%). Approximately 7.7% of patients had some trigeminal autonomic features, which are not permitted in the ICHD-3β criteria. Compared with the ICHD-2 criteria, the diagnostic rate under the new criteria increased from 65% to 85% in recently reported cases. Randomized control trials both for acute and prophylactic treatment are lacking. Based on observational studies, the most effective acute treatment is caffeine and prophylactic medications in use are lithium, caffeine and indomethacin. Without treatment, the disease course is usually protracted but spontaneous remission did occur in 12 patients (4.8%). In those treated with prophylactic agents, no recurrence was noted in 43% of patients, even following withdrawal of medication. Conclusions: The new ICHD-3β criteria are more sensitive and exhaustive for HH than the ICHD-2 criteria. Prophylactic treatment provides better outcomes; however, randomized controlled studies for treatment are needed to further verify the efficacy of the different drugs.